Considerations for the Prosthetic Dental Treatment of Geriatric Patients in Germany - Nitschke, Ina (J Clin Med, 2021)
Demographic changes in the industrialized countries require that dentists adapt to the growing and heterogeneous group of elderly patients and develop concepts for the dental care of fit, frail, and dependent old and very old people. In general, dental care for old and very old people should be based on their individual everyday life. As a result of demographic changes, improved oral hygiene at home, and the establishment of professional teeth and denture cleaning, tooth loss occurs increasingly in higher ages, which implies that first extensive prosthetic rehabilitation with fixed or/and removable dental prostheses is shifting to a higher average age than ever before. This phenomenon requires that the individual diseases, potential multimorbidity and polypharmacy, and associated limitations are taken into consideration. Against this background, the current survey aims to summarize epidemiological trends associated with tooth loss, using Germany as a highly representative country for demographic changes as an example. Furthermore, the current narrative summary outlines general principles that should be followed in dental care, treatment of geriatric patients, and outlines current therapeutic options in prosthetic dentistry.